2013
DOI: 10.1007/s12024-013-9504-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiothoracic ratio in postmortem computed tomography: reliability and threshold for the diagnosis of cardiomegaly

Abstract: The aim of this study was to evaluate the reliability of the cardiothoracic ratio (CTR) in postmortem computed tomography (PMCT) and to assess a CTR threshold for the diagnosis of cardiomegaly based on the weight of the heart at autopsy. PMCT data of 170 deceased human adults were retrospectively evaluated by two blinded radiologists. The CTR was measured on axial computed tomography images and the actual cardiac weight was weighed at autopsy. Inter-rater reliability, sensitivity, and specificity were calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…The authors agree that testing intra-rater or inter-rater reliability of IVC diameter measurements would have improved the methodological foundation of the study. However, a number of studies revealed excellent high intra-rater and inter-rater agreement regarding metric measurements on radiologic images [7,23,24]. Second, the level at which the diameter of the IVC was measured was selected subjectively.…”
Section: Discussionmentioning
confidence: 99%
“…The authors agree that testing intra-rater or inter-rater reliability of IVC diameter measurements would have improved the methodological foundation of the study. However, a number of studies revealed excellent high intra-rater and inter-rater agreement regarding metric measurements on radiologic images [7,23,24]. Second, the level at which the diameter of the IVC was measured was selected subjectively.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that among the different variables tested, body mass index (BMI) and heart dilatation influence the postmortem CTR [20]. The role of dilatation was not evaluated by Winklhofer et al [40] while cardiac dilatation and terminal central congestion was reported by Michiue et al [41] in cases of drowning, alcohol/sedative-hypnotic intoxication, and some SCDs. Jotterand [42] presented at the International Society of Forensic Radiology and Imaging meeting in 2017 a "new formula for CTR for the diagnostic of cardiomegaly on postmortem CT".…”
Section: Heart Weight and Sizementioning
confidence: 99%
“…In postmortem practice, the CTR value was first evaluated on PMCT by Winklhofer et al [40], who suggested a threshold of 0.57 as a cut-off of CTR to detect cardiomegaly with a specificity of 95%. Jotterand et al [20] evaluated the CTR on PMCT for normal hearts considering the normal reference values for the heart weight and observed an overestimation of the CTR measurements made on scout compared to axial view.…”
Section: Heart Weight and Sizementioning
confidence: 99%
“…However, to our knowledge, there are not any studies on the CV measurements on MPMCTA which includes comparisons with autopsy finding, although CV measurements on native postmortem CT scan already exist in some studies [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%